IMPLEMENTATION OF PEDAGOGICAL ETHICS IN FUTURE TEACHERS - P.Urisheva (Scholar Express Journals, 2023)
This article discusses the formation of the pedagogical behavior of future teachers. There are examples of teachers' ethics.
Keywords: professional ethics; pedagogical requirements; axiological skills